Control-oriented plasma modeling and controller design for reactive sputtering. (June 2021) - Woelfel, Christian; Oberberg, Moritz; Berger, Birk; Engel, Dennis; Brinkmann, Ralf Peter; Schulze, Julian; Awakowicz, Peter; Lunze, Jan
Abstract: The modeling and control of reactive sputtering processes to deposit aluminum oxide thin films by an RF driven magnetically-enhanced low-pressure plasma is investigated. The new model describes the nonlinear deposition process with respect to the reactive gas flow as the input and the plasma density as the output. The process behavior is characterized by an unstable and ambiguous behavior, where different plasma states refer to the same input value, whereas different input values can lead to the same plasma state. Based on the identified model the process can be classified by two process modes, which qualitatively determine the parametrization of a stabilizing pseudo-derivative feedback controller. A new controller design to achieve set-point following for the control loop with a specific transient behavior is proposed. Experiments are presented to validate the model and the control system.